Strategy For Improving Facilities And Infrastructure In Improving The Quality Of Education - Junita Nadila (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2021)
Abstract: This study aims to determine the strategy of improving educational facilityesÂ and infrastructur that will improve the quality of the school. This research method is a qualitative type with library analysis techniques. In this study, it shows that the strategy of improving facilities and infrastructure in improving the quality of education in schools emphasizes that the procurement and utilization of good and complete facilities and infrastructure, which in the strategy of improving facilities and infrastructure is very important to be carried out effectively and efficiently in order to create a complete school atmosphere and not be left behind because this infrastructure shows the results of a quality education in schools.Keywords: Strategic;management;facility and infrastructure;school qualityÂ Abstrak : Penelitian ini memiliki tujuan agar mengetahui strategi peningkatan dari sarana dan juga prasarana pendidikan yang baik, dengan begitu akan meningkatkan mutu pada sekolah tersebut. Metode penelitian ini berjenis kualitatif dengan tekhnik analisis pustaka Dalam penelitian ini menunjukkan bahwa strategi peningkatan sarana dan prasarana dalam meningkatkan mutu pendidikan di sekolah menekan kan bahwa pengadaan dan pendayagunaan pada sarana dan prasarana yang baik dan lengkap, yang mana dalam strategi peningkatan sarana dan prasarana sangat penting untuk dilakukan secara efektif dan efisien agar terciptanya suasana sekolah yang lengkap dan tidak tertinggal karena dari sarana prasarana ini menunjukkan hasil suatu mutu pendidikan di suatu sekolahKata Kunci: Management, Srategik, Sarana dan Prasarana, Mutu sekolah.